Recovery of maize (Zea mays L.) inbreds and hybrids from chilling stress of various duration: photosynthesis and antioxidant enzymes - Holá, Dana; Kocová, Marie; Rothová, Olga; Wilhelmová, Nad'a; Benesová, Monika (Journal of plant physiology, 2007)
The differences between two maize (Zea mays L.) inbred lines and their F1 hybrids in their response to chilling periods of various duration (1, 2, 3 or 4 weeks) and subsequent return to optimum temperatures were analysed by the measurement of the photosystem (PS) 1 and 2 activity, the photosynthetic pigments' content and the activity of antioxidant enzymes. The PS2 activity and the chlorophyll content decreased in plants subjected to 3 or 4 weeks of chilling, but not in those subjected to 1 or 2 weeks of chilling. This decrease was more pronounced in inbreds compared to their hybrids. The activity of superoxide dismutase did not much change with the increasing length of chilling period in the inbreds but decreased in the hybrids, the glutathione reductase activity increased in both types of genotypes but more in the inbred lines, while for ascorbate peroxidase and catalase the changes in parents-hybrids relationship did not show any specific trend. The PS1 activity and the carotenoids' content was not much affected.
Keywords: superoxiddismutasa; chlorofyl; genotyp; fotosystém II (proteinový komplex); glutathionreduktasa; Antioxidants; Genotype; kukuřice setá; Cold Temperature; Photosystem II Protein Complex; Inbreeding; fotosystém I (proteinový komplex); nízká teplota; inbreeding; fotosyntéza; rostlinné proteiny; antioxidancia; Superoxide Dismutase; Zea mays; katalasa; Photosynthesis; peroxidasy; Peroxidases; Plant Proteins; Chlorophyll; Hybridization, Genetic; Photosystem I Protein Complex; hybridizace genetická; Ascorbate Peroxidases; Catalase; Glutathione Reductase; askorbátperoxidasa